Zaburzenia odżywiania - problem wciąż aktualny = Eating disorders - an ongoing problem - Ewa Rzońca; Agnieszka Bień; Grażyna Iwanowicz-Palus (Kazimierz Wielki University, 2016)
Rzońca Ewa, Bień Agnieszka, Iwanowicz-Palus Grażyna. Zaburzenia odżywiania - problem wciąż aktualny = Eating disorders - an ongoing problem. Journal of Education, Health and Sport. 2016;6(12):267-273. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.198734 http://ojs.ukw.edu.pl/index.php/johs/article/view/4053         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 09.12.2016. Accepted: 09.12.2016.       Zaburzenia odżywiania - problem wciąż aktualny Eating disorders - an ongoing problem   Ewa Rzońca, Agnieszka Bień, Grażyna Iwanowicz-Palus     Zakład Podstaw Położnictwa, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Department of the Basics of Midwifery, Faculty of Health Sciences, Medical University of Lublin   Słowa kluczowe: zaburzenia odżywiania, ortoreksja, anoreksja, pregoreksja, bulimia, otyłość Key words: nutritional disorder, orthorexia nervosa, anorexia, pregorexia, bulimia nervosa, obesity     STRESZCZENIE Na przestrzeni ostatnich lat w krajach zachodnich nastąpił wzrost zachorowań na zaburzenia odżywiania, u podłoża, których podkreślane są zmiany społeczno-kulturowe. Zaburzenia odżywiania, takie jak ortoreksja, anoreksja, pregorekscja, bulimia czy otyłość to nieprawidłowe zachowania w obszarze nawyków żywieniowych, które prowadzą do znacznych zakłóceń masy ciała. Stanowią istotny problem zdrowotny, który dotyka głównie dziewczęta oraz młode kobiety, powodujący wiele negatywnych konsekwencji zarówno zdrowotnych, psychologicznych, jak i społecznych dla osoby chorej. Złożona etiologia zaburzeń odżywiania wymaga interdyscyplinarnego podejścia, uwzględniającego m. in. modyfikację stylu życia, w szczególności zachowań żywieniowych, wsparcie psychologiczne czy postępowanie farmakologiczne.     ABSTRACT Recent years have seen an increase in the occurrence of eating disorders in Western countries, with sociocultural changes being one of the main reasons for this trend. Eating disorders, such as anorexia, pregorexia, bulimia or obesity, are abnormal behaviours related to eating habits, which lead to serious disturbances in body weight. They are a major health problem mostly in girls and young women, negatively affecting their physical health, mental condition and social life in many different ways. The complex etiology of eating disorders requires an interdisciplinary approach, including methods such as change of lifestyle, in particular eating habits, psychological support and pharmacological treatment.